ANALISIS PENGARUH SERAT DAUN NANAS TERHADAP SIFAT MEKANIK PADA MATRIK POLYESTER DENGAN JENIS DAUN NANAS SMOOTH CAYENNE - Ilham Setyadi; Yuliyanto Yuliyanto; Nanda Pranandita (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Composite materials are new types of engineering materials consisting of two or more materials whose properties of each material differ from each. Thisresearch is done to assess theinfluence of the volume fraction of pineapple leaf fibers on tensile strength, modulus elasticity and composite impact strength using polyester matrix BQTN 157 with hand lay-up method withresearchojek in the form of pineapple leaf fiber composite with a immersion time of 2 hours and with NaOH 5% with variations in fiber volume fraction of 15%, 20%,%, 25%.%. Thehighest tensile strength K is found in the volume fraction of 25% with a tensile test strength value of 84.4 Mpa and the lowest tensile test strength is at a volume fraction of 15% with a tensile test strength value of 58.7 Mpa.. As for the highest elasticity modulus value is at a volume fraction of 25% which is 17933 Mpa and the lowest tensile test strength is at a volume fraction of 15% with a tensile test strength value of 16400 Mpa.. And for the highest impact strength composite with pineapple leaf fiber is found at a volume fraction of 25% with an average impact power value of 163.2 Kj / mm2 and the lowest impact strength value is in the fiber fraction of 15% with an average impact power value of 63.9 Kj / mm2.